Effects of intra-articular injection of mesenchymal stem cells associated with platelet-rich plasma in a rabbit model of osteoarthritis - Hermeto, L. C.; DeRossi, R.; Oliveira, R. J.; Pesarini, J. R.; Antoniolli-Silva, A. C. M. B.; Jardim, P. H. A.; Santana, A. E. [UNESP]; Deffune, E. [UNESP]; Rinaldi, J. C. [UNESP]; Justulin, L. A. [UNESP] (Funpec-editora, 2016)
The current study aims to evaluate the macroscopic and histological effects of autologous mesenchymal stem cells (MSC) and platelet-rich plasma on knee articular cartilage regeneration in an experimental model of osteoarthritis. Twenty-four rabbits were randomly divided into four groups: control group, platelet-rich plasma group, autologous MSC undifferentiated group, and autologous MSC differentiated into chondrocyte group. Collagenase solution was used to induce osteoarthritis, and treatments were applied to each group at 6 weeks following osteoarthritis induction. After 60 days of therapy, the animals were euthanized and the articular surfaces were subjected to macroscopic and histological evaluations. The adipogenic, chondrogenic, and osteogenic differentiation potentials of MSCs were evaluated. Macroscopic and histological examinations revealed improved tissue repair in the MSC-treated groups. However, no difference was found between MSC-differentiated and undifferentiated chondrocytes. We found that MSCs derived from adipose tissue and platelet-rich plasma were associated with beneficial effects in articular cartilage regeneration during experimental osteoarthritis.
Keywords: Chondrogenic differentiation; Chondral defect; Arthritis; Cellular therapy